The Experience of Commuters Facing Severe Traffic Congestion in The Jabodetabek Area - Hasanah, Linda Usfatul; Chotib, Chotib (Department of Urban and Regional Planning, Universitas Diponegoro, 2026)
Congestion that occurs in the Greater Jakarta metropolitan area is the result of an imbalance between road capacity and the number of vehicles crossing an area. According to data from the 2023 commuter survey, 79% of private vehicle users and 19.5% of public transportation users, the rest are non-motorized vehicle users. Congestion that occurs is not only due to an imbalance in road capacity and the use of motor vehicles, there are factors that affect severe congestion in Greater Jakarta, namely individual characteristic variables (gender, age, education, occupation, and income), mode of transportation (mode of transportation used and frequency of change of modes) and travel characteristics (distance traveled and travel time). Variables of distance traveled and travel time are important factors for severe congestion in Greater Jakarta. This study aims to analyze the influence and significance of each variable on the chances of severe congestion experienced by commuters in the Greater Jakarta area. This data was analyzed statistically descriptive and inferential. This study utilizes microdata from the 2023 Jabodetabek Commuter Survey from the Central Statistics Agency. The results of the analysis show that all the variables proposed in this study have a significant effect on the chance of severe congestion.